ANALISIS HUBUNGAN ANTARA TRUST, COMMITMENT, ECONOMIC SATISFACTION DAN NON-ECONOMIC SATISFACTION DALAM BUYER-SUPPLIER RELATIONSHIP DI SURABAYA - Arbhie Nugraha Hanafi; Fitri Novika Widjaja; Antonius Budhiman Setyawan (Perpustakaan Universitas Surabaya, 2018)
With the increase of complexity in the business development, companies are required to survive and win the existing competition in business. Working with other companies is one way that companies can take. The cooperative relationship between buyers and suppliers is one example of the relationship that can arise in the business world. There are several factors that can affect buyer-supplier relationship, such as trust, commitment, and satisfaction. This study aims to determine and analyze the influence of trust, commitment, economic satisfaction, and non-economic satisfaction towards buyer-supplier relationship in Surabaya. This research uses quantitative approach by using Structural Equation Modeling (SEM) method through Amos program. The data used in this study is the primary data obtained from the distribution of questionnaires. The samples of this study were selected using non-probability sampling technique, the target population characteristics are those who work in companies domiciled in Surabaya and work in the purchasing departmentor in some companies called procurementand have a working experience in that section for ± 1 year. The number of samples used were 120 samples. The results of this study indicate that trust, commitment, economic satisfaction, and non-economic satisfaction have positive relation in buyer-supplier relationship in Surabaya.